GROWTH TRAIT'S AND YIELD EVAIUATION OF ITALIAN MAIZE INBRED LINES BY FULL DIALLEL CROSS - & et al., Abed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
To evaluate five  maize inbred lines imported from Italy by  daillel and reciprocal crosses which predict from its, by estimate the heterosis ,general and specific combining ability effect(Gca,Sca,Rca), type of gene action and degree of dominance  for growth traits  and total yield. Field experiment was conducted during the two successive  seasons of 2013 , during spring  seasons full –diallel cross was carried out among inbred lines, In fall season a comparison experiment between the parents and the hybrids was carried by using randomized complete block design. The result show significant differences  for the  plant height (PH)(cm), ear height (EH)(cm) ,number of  leafs per plant(NLP) ,leaf area index(LA) ,the biomass(BI) and total yield per area(TY)(tan.h-1) which refer to high variation among the parents. The  inbred line Agostano  excel in TY (tan .h-1), NLP and  the BI, as such the DSP177  was excellence in ether traits  and the cross between  parents was deign high TY reach to 7.88 tan.h-1.The results of heterosis revealed the 20 cross in PH,15 cross in EH,14 cross in NLP and LAI, 17 cross in BI and 15 cross in TY  a positive direction desired for heterosis , best values for it  given from the  hybrid Hi39Antiguao x FLO1240 (128.9%) in TY . The genetic analyses emerged the greatest role of inheritable traits which to demonic effect and some for this inheritable to additive effect   where notes high significant for the GCA,SCA and RCA but the rate of the  Gca / Sca more loss  than one for all traits as well as the rate of Gca / Rca  except LAI in reciprocal cross which it more than one , as such the dominance genetic variance(δ2D)  which higher than the  additive genetic variance(δ2A), and high bored  sense heritability (h2bs%) ,and lower narrow  sense heritability (h2ns %)for the daillel cross all traits as well as the degree of dominance which more than one except the LA in reciprocal cross  , It can be conclude the possibility of benefit to breed the parents to produce diallel cross by  using the hybridization  method is the hybridization and  the  hybridization followed by selection to produce reciprocal cross  .